ANALISIS KELEMBAGAAN TERHADAP PELAKSANAAN PROGRAM DEVERSIFIKASI PANGAN DI PASURUAN - Teguh Sarwo Aji; Novi Itsna Hidayati (Fakultas Pertanian Universitas Yudharta Pasuruan, 2017)
Until now it  HAD a lot of institutions formed to participate in addressing the problem of providing  food for the people. Starting from the institution handling food producers, marketing and  distribution of food, food - re lated capital activities, food safety, food industry and other aspects of  food. There  was an institutional official government institutions, non - governmental pure, or which  was the formal and informal collaboration between government and society. This stud y aims to  identify local institutions that can be used to support the acceleration of food diversification  program; analyze the role of local institutions based on their potential to support the acceleration of  food diversification program in Pasuruan. In  areas of research results show that there are 27  (nineteen) of local institutions that have the potential to support the acceleration of food  diversification program. The institution consists of 4 institutional  family welfare programs, 4  village consultati ve body, 4 institutional farmer groups, 4 institutional study, 3 institutional youth  clubs and 4 farmers cooperative women. Based on the potential role of local institutions in  supporting the acceleration of food diversification program in Pasuruan shows t hat institutional  diversification  potentially support the Food program  was the first classification, namely the  family  welfare programs of  Village Gerbo,  village consultative body of  Gerbo,  village consultative body of Pucang  Sari ,  family welfare programs of  Pucang Sari, Farmers Group of Pucang Sari ,  family  welfare programs of  Village Suwayuwo,  f armers  g roup of Gerbo ,  Men  Jam'iah Tahlil  of  Pucang  Sari , Farmers Group  of Suwahyuwo ,  family welfare programs of  Pandaan Village, farmers  cooperative women  of G e rbo, farmers cooperative women  of  Pucang  Sari , NU  Moslem of  Pandaan,  NU  Moslem  of  Suwayuwo